Driving Sustainable Competitiveness Through Holistic Marketing and Esg: An Empirical Study on Msmes in Sukabumi Regency, Indonesia - Muchamad, Widy; Hurriyati, Ratih; Dirgantari, Puspo Dewi (Yayasan Sinergi Kawula Muda, 2026)
This study examines the influence of Holistic Marketing on the Sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Sukabumi Regency, with Environmental, Social, and Governance (ESG) as the mediation variable. This topic is very crucial because even though MSMEs are the backbone of the national economy, the majority still face significant obstacles in internalizing the sustainability values needed to maintain competitiveness in the digital economy era. In particular, this study fills a gap in the literature by exploring how a holistic marketing approach can be a key driver of ESG adoption in developing countries. Using a quantitative approach with the Structural Equation Modeling - Partial Least Squares (SEM-PLS) technique, data was collected from 200 MSME actors. The results of the analysis showed that Holistic Marketing had a significant positive effect on ESG (β = 0.566; p <0.001), indicating that comprehensive and digital-centric marketing strategies successfully improve ethical awareness and practices. ESG has a positive effect on Business Sustainability (β = 0.375; p <0.001) and has been shown to play a role as a partial mediator that strengthens the direct influence of Holistic Marketing on Business Sustainability (β = 0.329; p <0.001). The primary novelty of this study lies in the empirical evidence that the integration of digital-based holistic marketing and ESG represents a vital mechanism for MSME resilience in developing regions, a model that has been rarely explored in empirical research in Indonesia.